Les aliments génétiquement modifiés deviendraient-ils moins dangereux? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Novartis, une multinationale suisse, a mis au point un substitut